Preparation method and application of lithium iron phosphate / carbon composite material

By distributing carbon inside and between lithium iron phosphate particles to form conductive carbon bridges, the problems of low lithium-ion diffusion coefficient and low electrical conductivity of lithium iron phosphate materials are solved, thereby improving electrochemical performance and reducing costs.

CN114613965BActive Publication Date: 2025-01-10YICHANG BRUNP RECYCLING TECH CO LTD +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210281641.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-22
Publication Date
2025-01-10
Estimated Expiration
2042-03-22

AI Technical Summary

Technical Problem

Existing lithium iron phosphate materials suffer from low lithium-ion diffusion coefficients and low electrical conductivity, especially between internal particles and on the surface, which affects their electrochemical performance.

Method used

A lithium iron phosphate/carbon composite material was prepared by carbon doping and coating. By distributing carbon inside and between lithium iron phosphate particles, conductive carbon bridges were formed, which improved the transport channels for lithium ions and electrons.

Benefits of technology

It significantly improves the conductivity and electrochemical performance of lithium iron phosphate, reduces the amount of oxidant used, lowers the cost, and improves the lithium-ion diffusion coefficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114613965B_ABST
    Figure CN114613965B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of battery materials, and discloses a lithium iron phosphate / carbon composite material and a preparation method and application thereof, wherein the lithium iron phosphate / carbon composite material comprises carbon-doped lithium iron phosphate and a carbon layer coated on the surface of the carbon-doped lithium iron phosphate. The carbon-containing iron phosphate precursor synthesized by the present invention has carbon distributed inside the iron phosphate particles or between the particles, and further synthesizes the lithium iron phosphate material, which is more conducive to the formation of conductive carbon bridges between the inside of the lithium iron phosphate particles, between the inside of the particles and the surface layer, and between the particles, providing a transmission channel for lithium ions and electrons, thereby improving the electrochemical properties of the lithium iron phosphate, such as the conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a preparation method and application of a lithium iron phosphate / carbon composite material. Background Art

[0002] The preparation method of lithium iron phosphate is to use iron phosphate as a precursor, lithium carbonate as a lithium source, glucose or other organic carbon as a carbon source, and then grind, spray dry, sinter and other processes to obtain it. The commonly used synthesis method of iron phosphate in the market is precipitation, that is, ferrous sulfate, a byproduct of titanium dioxide process, is used as an iron source, ammonium dihydrogen phosphate or phosphoric acid as a phosphorus source, hydrogen peroxide is used as an oxidant, and ammonia or sodium hydroxide is used to adjust the pH of the reaction process to obtain precipitation. The amount of hydrogen peroxide used is generally 1.2-1.5 times the theoretical value, and the amount of hydrogen peroxide used greatly increases the cost of iron phosphate synthesis.

[0003] Due to the structural characteristics of lithium iron phosphate itself, it has defects such as low lithium ion diffusion coefficient and conductivity. To address this defect, surface carbon coating can effectively improve the ion and electron conductivity of the surface and between lithium iron phosphate particles; however, there are still problems of low lithium ion diffusion coefficient and conductivity between internal lithium iron phosphate particles and between internal particles and the surface layer, especially in order to increase the compaction density, there will be some large particles.

[0004] In order to solve the above problems, it is urgent to develop a preparation method and application of lithium iron phosphate that can improve the problems of low lithium ion diffusion coefficient and electrical conductivity between internal lithium iron phosphate particles and between internal particles and the surface layer. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a lithium iron phosphate / carbon composite material and a preparation method and application thereof, wherein the lithium iron phosphate / carbon composite material has electrochemical properties such as excellent electrical conductivity.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A lithium iron phosphate / carbon composite material comprises carbon-doped lithium iron phosphate and a carbon layer coated on the surface of the carbon-doped lithium iron phosphate.

[0008] Preferably, the first discharge specific capacity of the lithium iron phosphate / carbon composite material is 156-162 mAh / g.

[0009] Preferably, the initial charge and discharge efficiency of the lithium iron phosphate / carbon composite material is 97-99%.

[0010] A method for preparing a lithium iron phosphate / carbon composite material comprises the following steps:

[0011] (1) mixing an iron source solution and a phosphorus source, heating, adding a carbon source, continuing to heat, reacting, then adding an oxidant, continuing to react, separating the solid from the liquid, taking a solid phase, and obtaining a carbon-containing iron phosphate filter cake;

[0012] (2) pulping the carbon-containing ferric phosphate filter cake, performing solid-liquid separation, washing, and drying to obtain carbon-doped ferric phosphate dihydrate;

[0013] (3) The carbon-doped iron phosphate dihydrate, a lithium source and a carbon source are mixed and calcined to obtain the lithium iron phosphate / carbon composite material.

[0014] Preferably, in step (1), the iron source in the iron source solution is at least one of elemental iron, ferrous chloride, ferrous sulfate, ferric nitrate, ferrous acetate, ferrous phosphate, pyrite, waste ferric phosphate, and ferrophosphorus slag.

[0015] Further preferably, the iron element is one of iron powder and iron sheet.

[0016] Preferably, in step (1), the phosphorus source is at least one of phosphoric acid, phosphorous acid, sodium hypophosphite, ammonium hydrogen phosphate, ammonium dihydrogen phosphate or ammonium phosphate.

[0017] Further preferably, the phosphorus source is at least one of phosphoric acid, ammonium hydrogen phosphate, ammonium dihydrogen phosphate or ammonium phosphate.

[0018] Preferably, in step (1), the molar ratio of iron to phosphorus after the iron source solution and the phosphorus source are mixed is (0.92-1.03):1.

[0019] Further preferably, the iron-phosphorus molar ratio after the iron source solution and the phosphorus source are mixed is (0.97-1):1.

[0020] Preferably, in step (1), the temperature is raised to 40-50°C.

[0021] At a temperature of 40-50°C, carbon can be used as a crystal nucleus to gradually and slowly generate carbon-containing ferric phosphate dihydrate.

[0022] Preferably, in step (1), the carbon source is at least one of graphite, carbon nanotubes, graphene, carbon powder or acetylene black.

[0023] Further preferably, the carbon source is at least one of graphite, carbon nanotubes or carbon powder.

[0024] Preferably, in step (1), the reaction temperature is 70-100°C; further preferably, the reaction temperature is 80-95°C.

[0025] Preferably, in step (1), the reaction time is 1-2 h.

[0026] Preferably, in step (1), the oxidant is at least one of hydrogen peroxide, oxygen, sodium peroxide or ammonium persulfate.

[0027] More preferably, the oxidant is at least one of hydrogen peroxide and oxygen.

[0028] Preferably, in step (1), the temperature of the continued reaction is 70-100°C.

[0029] Preferably, in step (1), the reaction is continued for 2-10 hours, and more preferably, the reaction is continued for 4-8 hours.

[0030] Preferably, in step (2), the slurrying is to slurry the carbon-containing ferric phosphate filter cake and water at a solid-liquid ratio of 1 g:(5-10) mL to obtain a carbon-containing ferric phosphate slurry.

[0031] Preferably, in step (2), the washing is to wash the filtrate after solid-liquid separation until the conductivity of the filtrate is ≤500 μs / cm.

[0032] Further preferably, the washing is washing the filtrate after solid-liquid separation until the conductivity of the filtrate is ≤200 μs / cm.

[0033] Preferably, in step (2), the drying temperature is 60-120°C, and more preferably, the drying temperature is 90-110°C.

[0034] Preferably, in step (2), the specific surface area of ​​the carbon-doped iron phosphate dihydrate is 12-20 m 2 / g, Dv50 is 3.5-4.2cm.

[0035] Preferably, in step (3), the lithium source is at least one of lithium carbonate, lithium hydroxide or lithium dihydrogen phosphate.

[0036] Preferably, in step (3), the carbon source is at least one of glucose, sucrose, starch, carbon black or graphene.

[0037] More preferably, the carbon source is sucrose.

[0038] Preferably, in step (3), the calcination temperature is 650-800°C, and more preferably, the calcination temperature is 650-700°C.

[0039] Preferably, in step (3), the calcination time is 6-16 hours, and more preferably, the calcination time is 6-10 hours.

[0040] Preferably, in step (3), the calcination atmosphere is an inert atmosphere, and more preferably, the calcination atmosphere is a nitrogen atmosphere.

[0041] Preferably, in step (3), sand grinding and spray drying are also performed before calcination.

[0042] The present invention also provides a battery, comprising the above-mentioned lithium iron phosphate / carbon composite material.

[0043] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0044] 1. The carbon-containing iron phosphate precursor synthesized by the present invention has carbon distributed inside the iron phosphate particles or between the particles, and further synthesizing carbon-coated and carbon-doped lithium iron phosphate materials is more conducive to the formation of conductive carbon bridges between the lithium iron phosphate particles, between the particles and the surface, and between the particles, providing transmission channels for lithium ions and electrons, thereby improving the electrochemical properties of the lithium iron phosphate, such as the conductivity.

[0045] 2. In the present invention, after mixing the iron source solution and the phosphorus source, the temperature is increased and a carbon source is added, and the temperature is continued to be increased. Part of the divalent iron ions in the iron source solution will participate in the reaction. After a period of reaction, an oxidant is added and the reaction is continued to generate a carbon-doped orthorhombic iron phosphate dihydrate precursor. This process greatly reduces the amount of the oxidant used, and then the carbon-doped orthorhombic iron phosphate dihydrate, the carbon source, and the lithium source are calcined to prepare the lithium iron phosphate / carbon material. Since the precursor is the carbon-doped orthorhombic iron phosphate dihydrate, it is beneficial to the lithium embedding in the sintering process, and the lithium ion diffusion coefficient between the internal particles and the surface layer is improved. There is no need for dehydration, the cost is lower, and a lithium iron phosphate / carbon composite material with excellent electrochemical properties is prepared. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is a SEM image of carbon-doped iron phosphate dihydrate prepared in Example 1 of the present invention;

[0047] Figure 2 This is a schematic diagram of carbon distribution in the lithium iron phosphate / carbon composite material prepared in Example 1 of the present invention;

[0048] Figure 3 The XRD pattern of carbon-doped iron phosphate dihydrate prepared in Example 1 of the present invention;

[0049] Figure 4 This is a SEM image of ferric phosphate dihydrate prepared in Comparative Example 1 of the present invention;

[0050] Figure 5 The XRD diagram of iron phosphate dihydrate prepared in Comparative Example 1 of the present invention;

[0051] Figure 6 This is a SEM image of the lithium iron phosphate / carbon composite material prepared in Example 1 of the present invention;

[0052] Figure 7 This is the XRD diagram of the lithium iron phosphate / carbon composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0053] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0054] Example 1

[0055] The preparation method of the lithium iron phosphate / carbon composite material of this embodiment includes the following specific steps:

[0056] (1) preparing a mixed metal liquid: adding ferrous sulfate into a stirring tank to prepare a solution with an iron concentration of 35 g / L, then adding phosphoric acid to prepare a phosphorus concentration of 20 g / L, stirring evenly, and obtaining 70 L of a mixed metal liquid containing iron and phosphorus;

[0057] (2) Pour 70L of the prepared iron-phosphorus mixed metal liquid into a reaction container, turn on the stirring at 450rpm, heat to 90°C, add 82g of carbon nanotubes, heat to 90°C, keep at 90°C for 2h, and then start to drop hydrogen peroxide, the amount of hydrogen peroxide is 1.25kg. After the reaction is completed, separate the solid and the filtrate with a suction flask to obtain a carbon-containing iron phosphate filter cake;

[0058] (3) placing the separated carbon-containing iron phosphate filter cake into a pulping water cup, adding deionized water and stirring evenly, filtering, and then repeatedly washing with deionized water until the conductivity of the washing water is less than 500 μs / cm, stopping washing, taking the filter cake and spreading it and placing it in a 100° C. oven for drying to obtain carbon-doped iron phosphate dihydrate;

[0059] (4) 9.42 kg of carbon-doped ferric phosphate dihydrate, 1.88 kg of lithium carbonate and 580 g of sucrose were weighed, mixed, sand-milled and sprayed to obtain a powder, which was placed in a box furnace under a nitrogen atmosphere and calcined at 700° C. for 6 h to obtain a lithium iron phosphate / carbon composite material.

[0060] Example 2

[0061] The preparation method of the lithium iron phosphate / carbon composite material of this embodiment includes the following specific steps:

[0062] (1) preparing a mixed metal liquid: adding ferrous sulfate into a stirring tank to prepare a solution with an iron concentration of 39 g / L, then adding phosphoric acid to prepare a solution with a phosphorus concentration of 22.3 g / L, stirring evenly, and obtaining a mixed metal liquid containing iron and phosphorus;

[0063] (2) Pour 70L of the prepared iron-phosphorus mixed metal liquid into a reaction vessel, stir it at 450rpm, heat it to 90°C, add 457g of graphite, heat it to 90°C, keep it at 90°C for 2h, start to introduce oxygen, oxidize it for 2h, and after the reaction is completed, use a suction flask to separate the solid and the filtrate to obtain a carbon-containing iron phosphate filter cake;

[0064] (3) placing the separated carbon-containing iron phosphate filter cake into a pulping water cup, adding deionized water and stirring evenly, filtering, and then repeatedly washing with deionized water until the conductivity of the washing water is less than 500 μs / cm, stopping washing, taking the filter cake and spreading it and placing it in a 100° C. oven for drying to obtain carbon-doped iron phosphate dihydrate;

[0065] (4) 9.42 kg of carbon-doped ferric phosphate dihydrate, 1.88 kg of lithium carbonate and 580 g of sucrose were weighed, mixed, sand-milled and sprayed to obtain a powder, which was placed in a box furnace under a nitrogen atmosphere and calcined at 710° C. for 6 h to obtain a lithium iron phosphate / carbon composite material.

[0066] Example 3

[0067] The preparation method of the lithium iron phosphate / carbon composite material of this embodiment includes the following specific steps:

[0068] (1) preparing a mixed metal liquid: adding ferrous sulfate into a stirring tank to prepare a solution with an iron concentration of 38.4 g / L, then adding phosphoric acid to prepare a solution with a phosphorus concentration of 21.9 g / L, stirring evenly, and obtaining a mixed metal liquid containing iron and phosphorus;

[0069] (2) Pour 70L of the prepared iron-phosphorus mixed metal liquid into a reaction container, stir it at 450rpm, heat it to 90°C, add 457g of graphite, heat it to 90°C, keep it at 90°C for 2h, and then start to drop hydrogen peroxide, the amount of hydrogen peroxide is 1.36kg. After the reaction is completed, separate the solid and the filtrate with a suction flask to obtain a carbon-containing iron phosphate filter cake;

[0070] (3) placing the separated carbon-containing iron phosphate filter cake into a pulping water cup, adding deionized water and stirring evenly, filtering, and then repeatedly washing with deionized water until the conductivity of the washing water is less than 500 μs / cm, stopping washing, taking the filter cake and spreading it and placing it in a 100° C. oven for drying to obtain carbon-doped iron phosphate dihydrate;

[0071] (4) 9.42 kg of carbon-doped ferric phosphate dihydrate, 1.88 kg of lithium carbonate and 580 g of sucrose were weighed, mixed, sand-milled and sprayed to obtain a powder, which was then placed in a box furnace under a nitrogen atmosphere and calcined at 710° C. for 6 h to obtain a lithium iron phosphate / carbon composite material.

[0072] Comparative Example 1 (adding an oxidant before generating ferric phosphate dihydrate)

[0073] The preparation method of the lithium iron phosphate / carbon composite material of this comparative example comprises the following specific steps:

[0074] (1) preparing a mixed metal liquid: adding ferrous sulfate into a stirring tank to prepare a solution with an iron concentration of 35 g / L, then adding phosphoric acid to prepare a solution with a phosphorus concentration of 20 g / L, stirring evenly, and obtaining a mixed metal liquid containing iron and phosphorus;

[0075] (2) Pour 70L of the prepared iron-phosphorus mixed metal liquid into a reaction container, add 3.7kg of hydrogen peroxide to fully oxidize the divalent iron, and after oxidation, turn on the stirring and adjust it to 450rpm, add alkali solution to adjust the pH to 2.0, heat to 90°C and age for 4h, and use a suction flask to separate the solid and the filtrate to obtain an iron phosphate filter cake;

[0076] (3) placing the separated iron phosphate filter cake into a pulping water cup, adding deionized water and stirring evenly, filtering, and then repeatedly washing with deionized water until the conductivity of the washing water is less than 500 μs / cm, stopping washing, taking the filter cake and spreading it and placing it in a 100° C. oven to dry, thereby obtaining iron phosphate dihydrate;

[0077] (4) Weigh 7.54 kg of ferric phosphate dihydrate, 1.88 kg of lithium carbonate and sucrose, mix them, sand grind and spray to obtain powder, and then put the powder into a box furnace under a nitrogen atmosphere and calcine it at 700° C. for 6 hours to obtain a lithium iron phosphate / carbon composite material.

[0078] Physical and chemical results:

[0079] Table 1 shows the physical and chemical results of the ferric phosphate dihydrate products prepared in Examples 1, 2, 3 and Comparative Example 1. As shown in Table 1, the C contents in the ferric phosphate dihydrate products prepared in the examples are 1.024%, 4.981% and 5.149%, respectively.

[0080] Figure 1 This is a SEM image of carbon-doped ferric phosphate dihydrate prepared in Example 1 of the present invention; it can be seen from the image that the ferric phosphate in Example 1 is composed of prismatic and polygonal particles.

[0081] Figure 2 This is a schematic diagram of carbon distribution in lithium iron phosphate prepared in Example 1 of the present invention; Figure 2 The distribution of carbon in lithium iron phosphate can be obtained, and carbon is distributed inside iron phosphate particles or between particles.

[0082] Figure 3 This is the XRD diagram of carbon-doped iron phosphate dihydrate prepared in Example 1 of the present invention; it can be seen from the figure that the product obtained in Example 1 is orthorhombic iron phosphate dihydrate, which is different from the monoclinic iron phosphate dihydrate obtained by the general process; the bottom spectrum is the standard card spectrum of iron phosphate dihydrate.

[0083] Figure 4 This is a SEM image of ferric phosphate dihydrate prepared in comparative example 1 of the present invention; it can be seen from the image that the ferric phosphate dihydrate in comparative example 1 is formed by agglomeration of thin flake primary particles.

[0084] Figure 5 This is the XRD diagram of iron phosphate dihydrate prepared in comparative example 1 of the present invention. It can be seen from the figure that the product obtained in comparative example 1 is monoclinic iron phosphate dihydrate; the bottom spectrum is the standard card spectrum of iron phosphate dihydrate.

[0085] Figure 6 This is a SEM of lithium iron phosphate / carbon prepared in Example 1 of the present invention. It can be seen from the figure that the lithium iron phosphate in Example 1 is composed of spherical particles with rounded surfaces.

[0086] Figure 7 The XRD diagram of lithium iron phosphate / carbon prepared in Example 1 of the present invention is shown in FIG. From the diagram, it can be seen that the lithium iron phosphate obtained in Example 1 is pure phase and orthorhombic crystal.

[0087] Physical and chemical results:

[0088] Table 1 shows the physical and chemical results of the ferric phosphate dihydrate products prepared in Examples 1, 2, 3 and Comparative Example 1. As shown in Table 1, the C contents in the ferric phosphate dihydrate products prepared in the examples are 1.024%, 4.981% and 5.149%, respectively. Figure 2 This is a SEM picture of the iron phosphate in Example 1. It can be seen from the picture that the iron phosphate in Example 1 is composed of prismatic and polygonal particles. Figure 3 This is the XRD diagram of iron phosphate dihydrate in Example 1. It can be seen from the figure that the product obtained in Example 1 is orthorhombic iron phosphate dihydrate, which is different from the monoclinic iron phosphate dihydrate obtained by general process. Figure 4 This is a SEM image of the ferric phosphate dihydrate of Comparative Example 1. It can be seen from the image that the ferric phosphate dihydrate of Comparative Example 1 is formed by the agglomeration of thin primary particles. Figure 5 : is the XRD diagram of iron phosphate dihydrate of comparative example 1. It can be seen from the figure that the product obtained in comparative example 1 is monoclinic iron phosphate dihydrate.

[0089] Table 1 Physical and chemical results of ferric phosphate dihydrate products

[0090] Example 1 Example 2 Example 3 Comparative Example 1 Fe / % 29.3 29.05 29.16 29.13 P / % 16.6 16.29 16.44 16.51 Fe / P 0.978 0.988 0.983 0.978 C / % 1.257 4.981 5.149 0 Dv50 3.99 3.57 4.05 2.79 BET 13 17.5 15 45.8

[0091] Table 2 is a comparison of the amount of hydrogen peroxide used in Example 1 and the comparative example. It can be seen from the table that, under the same iron concentration and volume of liquid metal, the amount of hydrogen peroxide used in the comparative example is almost three times that of the example. Example 1 greatly reduces the amount of hydrogen peroxide used, reduces costs, and obtains orthorhombic iron phosphate dihydrate, which is conducive to lithium embedding.

[0092] Table 2 Comparison of hydrogen peroxide dosage between Example 1 and Comparative Example 2

[0093]

[0094] Electrochemical performance:

[0095] Figure 1 This is a schematic diagram of the carbon distribution of lithium iron phosphate particles of the present invention. There are carbon bridges inside the particles and a carbon coating layer on the surface of the particles. This carbon distribution can connect the grains inside the particles, the grains to the surface of the particles, and the particles to each other, providing lithium ion and electron transmission channels, thereby improving the electrochemical performance of lithium iron phosphate.

[0096] Table 3 shows the electrochemical performance of lithium iron phosphate batteries prepared in Examples 1, 2, 3 and Comparative Example, and the specific data are obtained by testing with an electrochemical workstation and other equipment. As shown in Table 2, the electrochemical performance of the lithium iron phosphate products prepared in the Examples is significantly better than that in Comparative Example 1, especially in Example 1.

[0097] Table 3 Comparison of electrochemical performance of lithium iron phosphate batteries

[0098] Electrochemical performance Example 1 Example 2 Example 3 Comparative Example 1 First discharge specific capacity (mAh / g) 159.2 157.8 156.4 153.4 First charge and discharge efficiency (%) 98.7 97.6 97.2 95.6 0.5C discharge specific capacity (mAh / g) 153 151.7 150.9 140 1C discharge specific capacity (mAh / g) 147.7 145.2 144.8 132.1 2C discharge specific capacity (mAh / g) 139.4 136 135.1 116.4 5C discharge specific capacity (mAh / g) 129.6 123 121 98.5 10C discharge specific capacity (mAh / g) 118.9 111.7 108.3 80.5

[0099] The present invention is not limited to the above-mentioned embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A method for preparing a lithium iron phosphate / carbon composite material, characterized in that: The following steps are involved: (1) mixing an iron source solution and a phosphorus source, heating, adding a carbon source, continuing to heat, reacting, then adding an oxidant, continuing to react, separating the solid from the liquid, taking a solid phase, and obtaining a carbon-containing iron phosphate filter cake; (2) pulping the carbon-containing ferric phosphate filter cake, performing solid-liquid separation, washing, and drying to obtain carbon-doped ferric phosphate dihydrate; (3) mixing the carbon-doped iron phosphate dihydrate, a lithium source and a carbon source, and calcining to obtain the lithium iron phosphate / carbon composite material; In step (1), the temperature for continuing the reaction is 70-100° C.; The lithium iron phosphate / carbon composite material comprises carbon-doped lithium iron phosphate and a carbon layer coated on the surface of the carbon-doped lithium iron phosphate; the lithium iron phosphate is orthorhombic lithium iron phosphate.

2. The preparation method according to claim 1, characterized in that: The first discharge specific capacity of the lithium iron phosphate / carbon composite material is 156-162 mAh / g.

3. The preparation method according to claim 1, characterized in that: The initial charge and discharge efficiency of the lithium iron phosphate / carbon composite material is 97-99%.

4. The preparation method according to claim 1, characterized in that: In step (1), the iron source in the iron source solution is at least one of elemental iron, ferrous chloride, ferrous sulfate, ferric nitrate, ferrous acetate, ferrous phosphate, pyrite, waste ferric phosphate, and ferrophosphorus slag; the phosphorus source is at least one of phosphoric acid, phosphorous acid, sodium hypophosphite, ammonium hydrogen phosphate, ammonium dihydrogen phosphate, or ammonium phosphate.

5. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of iron to phosphorus after the iron source solution and the phosphorus source are mixed is (0.92-1.03):1; and the reaction time is 2-10 hours.

6. The preparation method according to claim 1, characterized in that: In step (1), the carbon source is at least one of graphite, carbon nanotubes, graphene, carbon powder or acetylene black; and the oxidant is at least one of hydrogen peroxide, oxygen, sodium peroxide or ammonium persulfate.

7. The preparation method according to claim 1, characterized in that: In step (3), the lithium source is at least one of lithium carbonate, lithium hydroxide or lithium dihydrogen phosphate.

8. The preparation method according to claim 1, characterized in that: In step (3), the carbon source is at least one of glucose, sucrose, starch, carbon black or graphene.

9. A battery, characterized in that: It comprises a lithium iron phosphate / carbon composite material prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • High power iron phosphate ion battery material and preparation method thereof

    CN102760880A

  • Method for preparing lithium iron phosphate / carbon composite material

    CN108183234A